2017
DOI: 10.24326/asphc.2017.6.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Titanium on Growth of Very Early-Maturing Potato Cultivars

Abstract: A condition for achieving a high potato tuber yield on an early harvest is to provide plants with good growth conditions. In modern horticulture, plant growth stimulants have been gaining increasing importance. This study examined the effect of dose (0.2 dm 3 ha-1 or 0.4 dm 3 ha-1) and date (leaf development stage-BBCH 14-16, tuber formation stage-BBCH 41-43, leaf development stage and tuber formation stage) of Tytanit ® application (8.5 g Ti in 1 dm 3) on the growth of very early-maturing potato cultivars ('L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…According to Sawicka and Mikos-Bielak (1995), an increase in potato tuber yield may be associated with a decrease in levels of certain, but not all, minerals in tubers. Tytanit ® as a growth stimulant caused an increase in the plant height and aboveground plant biomass and tuber weight per plant (Wadas and Kalinowski, 2017a), and as the result an increase in the yield of new potatoes of 'Lord' and 'Miłek' cultivars (Kalinowski and Wadas, 2017), but did not affect the macroelement contents in tubers, except for sodium. Leaf-absorbed titanium is translocated to roots via phloem and accumulated in the chloroplasts (Kelemen et al, 1993;Lyu et al, 2017).…”
Section: Weather Conditions In Potato Growing Seasonmentioning
confidence: 94%
See 1 more Smart Citation
“…According to Sawicka and Mikos-Bielak (1995), an increase in potato tuber yield may be associated with a decrease in levels of certain, but not all, minerals in tubers. Tytanit ® as a growth stimulant caused an increase in the plant height and aboveground plant biomass and tuber weight per plant (Wadas and Kalinowski, 2017a), and as the result an increase in the yield of new potatoes of 'Lord' and 'Miłek' cultivars (Kalinowski and Wadas, 2017), but did not affect the macroelement contents in tubers, except for sodium. Leaf-absorbed titanium is translocated to roots via phloem and accumulated in the chloroplasts (Kelemen et al, 1993;Lyu et al, 2017).…”
Section: Weather Conditions In Potato Growing Seasonmentioning
confidence: 94%
“…Reducing the assimilation leaf area along with the increasing the chlorophyll a content and simultaneously decreasing the chlorophyll b content in leaves results in an increase in dry matter content in tubers (Sawicka et al, 2015). Tytanit ® caused an enlargement of the assimilation leaf area and an increase in chlorophyll content in leaves of very early potato cultivars (Wadas and Kalinowski, 2017b), however did not affect the content of dry matter in tubers. According to Sawicka and Mikos-Bielak (1995), an increase in potato tuber yield may be associated with a decrease in levels of certain, but not all, minerals in tubers.…”
Section: Weather Conditions In Potato Growing Seasonmentioning
confidence: 97%
“…The measurements were made on four successive randomized plants per plot. The assimilation area was measured by the weight method [36]. SLA was calculated as the ratio of assimilation area/weight of leaves [37].…”
Section: Determination Of Assimilation Area Chlorophyll Content and mentioning
confidence: 99%
“…Raskar and Lawares, 2013 , Clement et al, 2013 found that a low dose of Tytanit stimulated seed germination and early growth of seedlings, while higher doses caused an opposite effect. The available literature ( Cigler et al, 2010 , Giménez et al, 1990 , Hrubý et al, 2002 , Radkowski, 2013 , Wadas and Kalinowski, 2017b , Yaghoubi et al, 2000 ) suggests that titanium application has a beneficial effect on the processes of photosynthesis, with an increase in the concentration of chlorophyll in leaf blades, better nitrogen uptake by cells, and growth of the SPAD index exceeding 20%. In addition, one of the consequences of titanium application to plants is an increase in glucose production, which translates into faster synthesis of biopolymers such as cellulose and starch.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new effective methods and environmentally friendly solutions are needed to improve the health and quality of plants ( Ilieva and Vasileva, 2013 , Janas et al, 2013 , Serrano et al, 2004 , Szparaga et al, 2018 , Kocira et al, 2019 , Vasileva et al, 2017 ). One of such biostimulants is Tytanit ( Godlewska and Ciepiela, 2018 , Malinowska and Kalembasa, 2012 , Radkowski and Radkowska, 2013 , Radkowski et al, 2015 , Wadas and Kalinowski, 2017a ), the active ingredient of which is titanium (Ti). This chemical element is a micronutrient having a positive effect on plant biochemistry, supporting processes leading to an acceleration of plant growth and to an increase in the production of biomass ( Kužel et al, 2003 , Lyu et al, 2017 , Radkowski and Radkowska, 2010 ).…”
Section: Introductionmentioning
confidence: 99%